Process-Based Organisation Design for Public Hospital Efficiency - Mosia, A.N.; Nyaka, B.C.D. (The South African Journal of Industrial Engineering, 2025)
The central idea of process-based organisation design is that organising a firm around core business processes leads to efficiency. We adopted a qualitative research approach in this study to investigate whether the implementation of a process-based organisation design would be advisable in public hospitals. The data comes from a database compiled by the Statistical Office of the Gauteng Department of Health and from a written survey questionnaire that was sent to the chief executive officers of 15 hospitals. We used statistical analysis to measure hospital efficiency, and factor analysis and regression analysis to test our hypothesis. The data was mined from the value stream of each hospital. Our finding is that a high degree of process-based organisation in hospitals had a moderate but significant positive effect on their efficiency. The main implication is that hospitals should implement process-based operations in order to improve their efficiency. However, to achieve positive effects on efficiency, it would be important to observe some implementation rules.